Do school physical activity policies and programs have a role in decreasing multiple screen time behaviours among youth? - KATAPALLY, TARUN REDDY; Laxer, Rachel; Qian, Wei; Leatherdale, Scott T. (Elsevier, 2017)
Screen time in youth has been associated with a wide range of poor health outcomes. Evidence indicates the need to develop physical activity (PA) school policies and programs that are aimed at decreasing youth screen time behaviours. This study aims to understand the association between PA policies and programs embedded into the functioning of 89 schools across two provinces in Canada and multiple screen time behaviours. As part of the COMPASS Study, a total of 44,861 youth aged between 13 and 18 years and belonging to 89 schools in two Canadian provinces completed a validated questionnaire for health behaviours and outcomes data. PA policies and programs were measured using the School Policies and Practices Questionnaire, completed by the relevant school administrator. Participation in before-school, noon hour, or after-school intramural programs, participation in varsity sports, and access to indoor areas of PA during non-instructional time, was associated with significantly lower multiple screen time behaviours across both provinces. With exposure to multiple electronic and digital devices only predicted to increase among youth in the future, there is a need to conceptualize and integrate school-based screen time reducing PA policies and programs into the regular functioning of the schools.
The final publication is available at Elsevier via http://dx.doi.org/10.1016/j.ypmed.2017.11.026 © 2018. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: Adolescent health; Physical activity; School health; School policies; Screen time